2017
DOI: 10.3847/1538-4357/aa81d4
|View full text |Cite
|
Sign up to set email alerts
|

A Large-scale Plume in an X-class Solar Flare

Abstract: Ever-increasing multi-frequency imaging of solar observations suggests that solar flares often involve more than one magnetic fluxtube. Some of the fluxtubes are closed, while others can contain open field. The relative proportion of nonthermal electrons among those distinct loops is highly important for understanding the energy release, particle acceleration, and transport. The access of nonthermal electrons to the open field is further important as the open field facilitates the solar energetic particle (SEP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Although the coarse angular resolution of the detectors we use for imaging does not allow us to derive an accurate height of the HXR source above the limb as in, e.g., Krucker et al (2015), we assume that it is likely a footpoint source located at chromospheric heights. At progressively lower frequencies, the MW sources extend higher in the corona, indicative of non-thermal electrons extending to higher heights where the magnetic field is relatively low, which is in line with earlier observations (Fleishman et al, 2017(Fleishman et al, , 2018a.…”
Section: Multi-wavelengths Observationsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the coarse angular resolution of the detectors we use for imaging does not allow us to derive an accurate height of the HXR source above the limb as in, e.g., Krucker et al (2015), we assume that it is likely a footpoint source located at chromospheric heights. At progressively lower frequencies, the MW sources extend higher in the corona, indicative of non-thermal electrons extending to higher heights where the magnetic field is relatively low, which is in line with earlier observations (Fleishman et al, 2017(Fleishman et al, , 2018a.…”
Section: Multi-wavelengths Observationsupporting
confidence: 91%
“…Glesener and Fleishman (2018) studied the non-thermal electrons in a flare-jet configuration and found an equipartition of the non-thermal energies between populations in the closed and open magnetic flux tubes. Closed flaring flux tubes can represent rather large reservoirs of highenergy electrons located either nearby (Kuroda et al, 2018) or far away from Fleishman et al (Fleishman et al, 2017) the main flare acceleration sites, possibly providing the seed population for solar energetic particles (SEPs). Fleishman et al (2011Fleishman et al ( , 2013Fleishman et al ( , 2016a probed the acceleration sites using MW observations and concluded that the acceleration regime was consistent with stochastic acceleration, while Fleishman et al (2018b) extended in time the studies of Fleishman et al (2016b) and Kuroda et al (2018) to quantify the acceleration and transport of the nonthermal electrons in the 3D domain.…”
Section: Introductionmentioning
confidence: 99%
“…Similar phenomena of radio sources that lack corresponding EUV/X-ray signatures in solar flares have been frequently reported in the literature (Chen et al 2013(Chen et al , 2018Fleishman et al 2017;Kuroda et al 2018). One of the most notable is dm-λ type III radio bursts: despite that recent dynamic spectroscopic imaging with high centroiding accuracy allows to precisely map detailed trajectories of type-III-burst-emitting electron beams propagating along newly reconnected magnetic flux tubes with arcsecond-scale accuracy, no corresponding loop-like structures have been found in high-resolution SDO/AIA EUV imaging data (Chen et al 2013(Chen et al , 2018.…”
Section: Lack Of Density Compression Signature In Euvsupporting
confidence: 82%
“…One of the most notable is dm-λ type III radio bursts: despite that recent dynamic spectroscopic imaging with high centroiding accuracy allows to precisely map detailed trajectories of type-III-burst-emitting electron beams propagating along newly reconnected magnetic flux tubes with arcsecond-scale accuracy, no corresponding loop-like structures have been found in high-resolution SDO/AIA EUV imaging data (Chen et al 2013(Chen et al , 2018. Another type of such phenomena are microwave gyrosynchrotron sources (emitted by nonthermal electrons of hundreds of keV) that sometimes lack observable counterparts in EUV and/or X-rays, which are often shown to occupy large, tenuous coronal loops (Fleishman et al 2017;Kuroda et al 2018). Interpretation for such "EUV/X-ray-invisible" radio sources has been largely along the same line of argument: the LOS column depth or emission measure associated with the radio-emitting plasma is insufficient for the source to be observed as distinguishable features against the background by current EUV/X-ray instrumentation.…”
Section: Lack Of Density Compression Signature In Euvmentioning
confidence: 99%
“…Ramaty 1969;Klein 1987;Raulin et al 1999;Kaufmann et al 2004;Luthi et al 2004;Silva et al 2007;Trottet et al 2011;Wu et al 2016;Song et al 2016), these observations have been explained in terms of enhanced Razin suppression (with extremely high density of ambient plasmas), enhanced self-absorption effect (assuming a high density of energetic electrons), or enhanced absorption by cool plasmas outside the source. For example, it has been proposed that ν p of tens of GHz is due to the Razin effect (selfabsorption) when the thermal (nonthermal) electron density is over 10 11 cm −3 (10 9 cm −3 ) for magnetic filed of several hundred gauss (Klein 1987;Klein et al 2010;Melnikov et al 2008;Fleishman et al 2011Fleishman et al , 2017Grechnev et al 2017). However, in most of these studies a single power-law energy distribution of non-thermal electrons was assumed.…”
Section: Summary and Discussionmentioning
confidence: 99%